Ultrasound-Guided Selective Bronchial Intubation: A Feasibility Study in Pediatric Animal Model - Gomes, Sara Hora; Miranda, Alice; Pêgo, José Miguel; Costa, Patrício S.; Correia-Pinto, Jorge (Frontiers in Medicine, 2022)
Objective: Selective one-lung ventilation used to optimize neonatal and pediatric surgical conditions is always a demanding task for anaesthesiologists, especially during minimally invasive thoracoscopic surgery. This study aims to introduce an ultrasound-guided bronchial intubation and exclusion technique in a pediatric animal model. Methods: Seven rabbits were anesthetized and airway ultrasound acquisitions were done. Results: Tracheal tube progression along the trachea to the right bronchus and positioning of the bronchial blocker in the left bronchus were successfully done with consistent ultrasound identification of relevant anatomical structures. Conclusions: The study provided a new application of ultrasound in airway management. More advanced experimental studies are needed since this technique has the potential for translation to pediatric anesthesia.